THE EUROPEAN EXPERIENCE OF STATE SUPPORT FOR ENTREPRENEURSHIP AND POSSIBILITIES OF ITS ADAPTATION IN UKRAINE IN THE CONTEXT OF EUROPEAN INTEGRATION - Zhuk, Olha; Kosmirak, Andrii (Public Management and Policy, 2026)
The article examines how the countries of the European Union build their approaches to supporting small and medium-sized businesses, and how this experience can be useful for Ukraine, which is currently moving towards rapprochement with the European community. The choice of topic is dictated by the fact that our state is going through a difficult period of simultaneous restructuring of the legal field to meet the requirements of the EU and the search for real, rather than declarative, levers for the revival of entrepreneurial activity – and this is happening in conditions when the economy is under the pressure of war and already needs to understand post-war recovery. The author sets the goal of comparing specific tools used by Poland, Germany and Estonia to develop entrepreneurship, and to find out what exactly from this arsenal can take root on Ukrainian soil. A comparison of the experience of EU countries has shown that the greatest importance is not the number of support programs, but their practical accessibility for a particular entrepreneur. Among the effective tools are grants through specialized agencies, simplified taxation for those who are just entering the market, electronic services that replace queues in offices, a network of incubators and clusters. Ukraine has already implemented some elements of this approach: “e-Work”, “Own Business”, “Action.Business”, credit guarantees – these are not just names, they are backed by thousands of people who have received real assistance. But the problem is that these initiatives exist more as islands than as parts of a single mechanism. The regulatory environment remains unstable, at the local level, there is a shortage of institutions capable of providing comprehensive support to an entrepreneur at all stages of business development, and access to financial resources – both grant and credit – for the vast majority of small business entities remains an exception rather than an established practice. In conclusion, the author emphasizes that reforming the domestic business support system requires not mechanical copying of foreign models, but a thoughtful combination of the best European developments with an understanding of the realities in which the Ukrainian economy operates.